Pola Interaksi Interkomunal Umat Beragama di Kota Banda Aceh - Muhammad Sahlan (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
Abstract: Intercommunity interaction among religious believer happened in two forms, one is on daily basis and another is associational. Daily interaction is significant, although it does not guarantee the creation of religious harmony among believers of various religions. Meanwhile associational interaction has a role in preventing religious conflict. However, intercommunity interaction in Banda Aceh city happens mainly in daily basis interaction compare to associational. The imbalance in interaction pattern will result in communication between religious believer on civil society and elite level hindered. The implication of this is supporters or superstructure of peace and religious harmony in Banda Aceh is fragile. Abstrak: Interaksi interkomunal umat beragama terjadi dalam dua bentuk, yaitu keseharian dan asosiasional. Interaksi keseharian penting, namun tidak menjamin terciptanya kerukunan antar umat beragama. Sementara interaksi asosiasinal berperan dalam mencegah terjadinya konflik keagamaan. Interaksi interkomunal antar umat beragama di Kota Banda Aceh lebih sering terjadi dalam bentuk keseharian dibanding asosiasional. Ketimpangan pola interaksi seperti ini menyebab komunikasi antar umat beragama di tingkat menengah (civil society) dan atas (elite) tidak berjalan dengan baik. Akibatnya basis pendukung atau suprastruktur perdamaian dan keharmonisan beragama di Kota Banda Aceh menjadi rapuh